Sustainable seagrass management based on bioecological values in Sekotong - Jaswadi Jaswadi; Windy Zaerani; Solihin Rahmat (Journal of Biology, Environment, and Edu-Tourism, 2025)
Seagrass ecosystems play a crucial bioecological role in maintaining coastal stability, yet their management at the local level continues to face significant challenges. This study aims to analyze the conditions, threats, and bioecological aspects that underpin sustainable seagrass management in Sekotong. A case study approach was employed, using semi-structured interviews with purposive sampling, with the West Lombok Marine and Fisheries Office (DKP) as the key informant. The literature review was selected based on criteria focusing on seagrass bioecology, ecosystem threats, and coastal management. Data were analyzed through reduction, categorization, and synthesis. The results show that while some areas retain stable seagrass cover (supported by mangrove/coral rehabilitation), other areas are vulnerable to degradation from marine tourism, increased sedimentation, and declining water quality. Bioecologically, species such as Enhalus acoroides, Thalassia hemprichii, and Cymodocea rotundata function as habitat providers, blue-carbon storage, and substrate stabilizers, but their resilience is heavily influenced by ecological pressures. The study concludes that effective seagrass management requires integrating bioecological data, regulating marine tourism, and enhancing coordination between the Regency and Provincial DKP. This research underscores the need for an integrated monitoring system and further provincial-level research to strengthen future conservation policymaking.